Relationship between time domain and frequency domain strain signal - Application to real data / A. A. A. Rahim ... [et al.] - A. Rahim, A. A.; Abdullah, S.; K. Singh, S. S.; Nuawi, M. Z. (Faculty of Mechanical Engineering Universiti Teknologi MARA (UiTM), 2018)
This paper presents the behaviour of time domain and frequency domain signal for fatigue signal based on the parameters used in each domain. Frequency domain analysis were used in noise signal applications. For structures that are subjected to irregular and random loading, the general problem faced are the complicated in statistical in term of characteristic. Especially, in amplitudes and total damage distribution obtained from number of cycles count. The traditional method of rainflow cycle counting were compared with PSD-based analysis. It is shown that the component of system can be computed by using transfer function of component and PSD of excitation strain. The statistical analysis are used to see the behaviour of the signal in time domain. It can be seen that bracket component is more critical compared to suspension component. The analysis continued with verifying the developed fatigue data editing in order to have the good relation with frequency domain analysis as the area under the PSD graph shows the energy contained in the particular signals independently. The linear relationship between the two parameters with R-square value measured are high, up to 0.8 for suspension component and 0.97 for bracket component. Thus, it has been suggested that frequency domain analysis can then be used in the time domain fatigue testing as the strong relationship obtained for both parameter used.